2011
DOI: 10.1152/physiolgenomics.00044.2011
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling and network analysis of the murine angiotensin II-induced abdominal aortic aneurysm

Abstract: We sought to characterize temporal gene expression changes in the murine angiotensin II (ANG II)-ApoE-/- model of abdominal aortic aneurysm (AAA). Aortic ultrasound measurements were obtained over the 28-day time-course. Harvested suprarenal aortic segments were evaluated with whole genome expression profiling at 7, 14, and 28 days using the Agilent Whole Mouse Genome microarray platform and Statistical Analysis of Microarrays at a false discovery rate of <1%. A group of angiotensin-treated mice experienced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 44 publications
10
52
0
Order By: Relevance
“…Ontologic pathway enrichment of significant genes was performed as previously described 24 . Briefly, numerous genes differentiated scr-miR-treated PPE-induced AAA from scr-miR-treated sham-control aorta.…”
Section: Resultsmentioning
confidence: 99%
“…Ontologic pathway enrichment of significant genes was performed as previously described 24 . Briefly, numerous genes differentiated scr-miR-treated PPE-induced AAA from scr-miR-treated sham-control aorta.…”
Section: Resultsmentioning
confidence: 99%
“…These analyses have demonstrated that AngII increases the abundance of a wide spectrum of genes for inflammation, immunity, matrix degeneration, apoptosis, cell cycling, angiogenesis and signalling pathways [46,47]. Another noteworthy attribute is that these analyses reveal that the pattern of gene abundance differs widely during progressive intervals of AngII infusion.…”
Section: Mechanisms Of Ras In Aaasmentioning
confidence: 95%
“…Recent transcriptional profiling and network analyses of mouse AngII-induced AAAs have provided comprehensive information regarding this aneurysmal disease [46,47]. These analyses have demonstrated that AngII increases the abundance of a wide spectrum of genes for inflammation, immunity, matrix degeneration, apoptosis, cell cycling, angiogenesis and signalling pathways [46,47].…”
Section: Mechanisms Of Ras In Aaasmentioning
confidence: 99%
“…EGFR has been implicated in various vascular disorders including hypertension (252,253) and the development and progression of abdominal aortic aneurysms (523). Treatment of ANG II-infused mice with erlotinib attenuates vascular hypertrophy and perivascular fibrosis independent of alterations in blood pressure (536).…”
Section: Role Of Egfr In the Vasculaturementioning
confidence: 99%